Piver Type II vs. Type III Hysterectomy in the Treatment of Early-Stage Cervical Cancer: Midterm Follow-up Results of a Randomized Controlled Trial - Sun, Hengzi; Cao, Dongyan; Shen, Keng; Yang, Jiaxin; Xiang, Yang; Feng, Fengzhi; Wu, Lingying; Zhang, Zhenyu; Ling, Bin; Song, Lei (Frontiers in Oncology, 2018)
Introduction: With the expansion of value-based medicine, we explore whether using type III hysterectomy to treat low-risk, early-stage cervical cancer constitutes overtreatment. In present study, we evaluate the midterm safety and postoperative quality of life of patients who underwent type II hysterectomy versus type III hysterectomy with systematic lymphadenectomy for low-risk early-stage cervical cancer (International Federation of Gynecology and Obstetrics (FIGO) IA2-IB1; maximum tumor diameter ˂2 cm). Patients and methods: The main study was a multicenter, phase III, randomized controlled trial (NCT02368574, https://www.clinicaltrials.gov/ct2/show/NCT02368574). Patients meeting the criteria were randomly divided into type II and type III hysterectomy groups between 2015 and March Midterm outcomes were analyzed at 36 months after the first eligible patient was enrolled. The primary end point was disease-free survival (DFS), and the secondary end point was postoperative quality of life. Results: A total of 97 patients were preliminarily enrolled, 93 of whom were included in the final analysis. The general information of the two groups did not differ. The 2-year DFS rate in the type II group was 100% compared with 97.9% in the type III group (P>0.05). Compared to the type III group, the patients who underwent type II hysterectomy showed a shorter surgical time (163 ± 18.8 min vs. 226 ± 16.4 min, P=0.014), less intraoperative blood loss (174 ± 27.7 ml vs. 268 ± 37.4 ml, P=0.047), less postoperative urinary retention (5/46 vs. 11/47 cases, P=0.109), and milder bladder injuries. The postoperative symptom experience scores of the type II group were significantly lower than those of the type III group. Moreover, the postoperative sexual/vaginal functioning and lubrication scores of the type II group were significantly lower than those of the type III group in subgroup analyses of patients who did not undergo postoperative chemoradiotherapy. Sexual apprehension scores were increased postoperatively in both groups. Conclusion: Based on the midterm analysis, the two groups show considerable security within two years after surgery, but long-term security requires further analysis. Type II hysterectomy can effectively reduce the surgical time and intraoperative blood loss, decrease postoperative complications, and improve the quality of life of early-stage cervical cancer patients.